Polyserositis: An Extremely Rare Life-Threatening Manifestation of Pheochromocytoma - Maryam Heidarpour; Mohammad Ali Haghighatpanah; Hassan Rezvanian; Motahare Yadegarfar; Amir Mohammad Mozafari; Mehrbod Vakhshoori; Davood Shafie (Case Reports in Endocrinology)
The pericardium is an uncommon site for manifestation of pheochromocytoma. Herein, the case of a 57-year-old man with cardiac tamponade is presented. Pericardiocentesis was performed, and the vital signs were stabilized afterwards. An abdominal computed tomography (CT) scan illustrated a nonhomogeneous right adrenal mass suspicious of pheochromocytoma, planned for right adrenalectomy. He recovered well after surgery, and his subsequent follow-ups did not reveal any complications.